ASUPAN KARBOHIDRAT DAN SERAT BERHUBUNGAN DENGAN LEMAK TUBUH REMAJA SMPN 16 JAKARTA - Nadiyah, Nadiyah; Andriani, Nova (Jurnal Nutrire Diaita (Ilmu Gizi), 2017)
The purpose of the study is to explore the relationship between nutrient intakes, physical activity and percentage of body fat in a group of adolescents. This cross-sectional study was carried out with 62 adolescents aged 13 to 14 years old; 34 girls (54,8%) and 28 boys (45,2%). Energy, macronutrients and vitamin D intake were assessed by two non-consecutive-24 hour food recalls. Calcium intake was assessed by a semi-quantitative food frequency questionnaire (SQ-FFQ), physical activity was assessed by Physical Activity Level (PAL) 2 x 24 hours and percentage of body fat was measured by bioelectrical impedance analysis (BIA). BIA measurements were taken at least 2 hours after meals. The mean age was 13,2 Â± 0,4 years. Mean percentage body fat was 22,2 + 5,9 %. In bivariate analysis, negative correlations were found between calcium intake (p= 0,002), fiber intake (p=0,009), physical activity (p= 0,016) and body fat. In multivariate analysis, fiber intake showed a negative correlation (Î² = -8,397, p = 0,001) and carbohydrate intake (Î² = 13,053, p = 0,003) showed a positive correlation with body fat, adjusted by age and sex. In conclusion, carbohydrate intake has a positive relationship with body fat and fiber intake has a negative relationship with body fat in adolescents.Keywords : body fat, adolescents, carbohydrate intake